Association between painful physical symptoms and clinical outcomes in East Asian patients with major depressive disorder: a 3-month prospective observational study - Ang, Q.Q.; Wing, Y.K.; He, Y.; Sulaiman, A.; Chiu, N.Y.; Shen, Y.C.; Wang, G.; Zhang, C.; Lee, K.H.; Singh, P.; Granger, R.E.; Raskin, J.; et al. (2009)
Aims: Reports from non-Asian populations indicate that painful physical symptoms (PPS) are associated with poorer clinical and functional outcomes in major depressive disorder (MDD). The purpose of this study is to report comparative changes in disease severity, treatment patterns and quality of life observed in East Asian patients with MDD, with and without PPS, as assessed prospectively over a 3-month observation period. Methods: This observational study enrolled 909 patients with MDD in psychiatric care settings in China, Hong Kong, Korea, Malaysia, Singapore and Taiwan. Patients were classified as PPS positive (PPS+) or negative (PPS)) based on mean modified Somatic Symptom Inventory scores of 2 or < 2 respectively. The Clinical Global Impression of Severity (CGI-S) and 17-item Hamilton Depression Rating Scale (HAMD(17)) determined depression severity; a visual analogue scale (VAS) determined pain severity; and the EuroQoL (EQ-5D) assessed well-being after 3 months observation. Results: Of the 909 enrolees, 355/471 (75.4) of PPS+ patients and 363/438 (82.9) of PPS) patients completed the study (p = 0.006). PPS+ patients improved less than PPS) patients on depression, pain and quality of life measures during the study (HAMD17 p < 0.001, CGI-S p < 0.001, VAS p = 0.008 and EQ-5D p = 0.004). Fewer PPS+ patients (46.5) achieved remission compared with PPS) patients (69.4, p < 0.001). Conclusion: As the presence of PPS is associated with poorer outcomes in East Asian MDD patients, clinical management should aim to address both the mental and PPS associated with MDD.